Social Media in Indonesia: Communication Network Analysis on Twitter Concerning the Issues of the Disbursement of Retirement Insurance - Arswendi, Alif; Prayudi, Prayudi; Susilo, M. Edy (Jurnal Paradigma, 2024)
The government creates a retirement insurance program for workers to prepare for their lives when they retire. However, the regulation draft No. 20 of 2022 in one of the articles stipulates that payment of the program can only be disbursed after a worker reaches the age of 56. This has caused many reactions of rejection from various parties, especially workers. In the real world, this rejection also occurs in the social media network Twitter. Therefore, this study aims to determine the network structure and the actors' roles in the communication network with the old age security editor on social media Twitter within February 12 – 18, 2022. This research uses descriptive quantitative methods and is analyzed using Social Media Network Analysis. The theory used was the theory of communication networks. Data was collected and analyzed using NodeXL and Netlytic software. The old-age security communication network has become a trending topic because of the many tweets users provide for different purposes. This shows that a hashtag in social media conveys the community's voice against government policies and can also be used for other interests.